Think tanks, Tories and the austerity discourse coalition - Hartwig Pautz (Policy & Society, 2018)
Political parties change their policy positions for a variety of reasons. Among these can be changing interpretations of economic or other kinds of knowledge. The article investigates whether think tanks, as producers, synthesisers and disseminators of knowledge, may have contributed to changes in the British Conservative Party’s positions on public spending, debt and deficit following the Global Financial Crisis and the onset of the Great Recession between 2008 and 2009. The article does not seek to attribute causality to think tanks’ activities and the Conservatives’ changing positions on public spending. However, it proposes that think tanks were relevant actors in the British ‘austerity discourse coalition’ and were, more specifically, relevant for the Conservatives’ adoption of a strict austerity agenda. The article also emphasises that think tanks should be considered as relevant actors in any analysis of the link between the cognitive dimension of public policy and political action.